(3GdEWGQ GdbGfhfj ddJbGVj GdeOfj YHQ GdEfJQfJ (B:s (3OQGSI JMdjdjI ebGQfI (B= The legal framework of civil litigation via internet : analytical and comparative study /s - (3SdjeGf, OGOjGQ MejOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2015)
(3jYO ehVhY GdJbGVj GdeOfj YHQ GdEfJQfJ ef GdehVhYGJ GdMOjKI GdJj XgQJ YbH EbMGe GdhSGFd GdJcfhdhLj faSgG aj EOGQI GdYed GdbVGFj, Ke eG dHK Cf ChLOJ bhGfjf GdeQGabGJ GdMOjKI ZWGA JTQjYjG dgG aj HYV GdHdOGf GdeJWhQI JcfhdhLjG hXgQJ JLdjGJg MJi aj HYV GdHdOGf GdYQHjI ef NdGd ejcfI GdJbGVjQ Ydi GdQZe ef YOe hLhO JfXje JTQjYj dgPG GdehVhY(B. (3hMjK Cf TcdjI GdELQGAGJ GdbVGFjI GdJj JQcRJ daJQI WhjdI HGdcJGHI GdJbdjOjI Ydi GdeMQQGJ GdhQbjI hHWdGfgG YfO YOe eQGYGJgG cGfJ JTcd GdYbHI GdCSGSjI dedGMbI QcH GdJWhQ GdJcfhdhLj aj eLGd GdYed GdbVGFj ef NdGd GdGSJaGOI ef JcfhdhLjG GdMGShH hGdEfJQfJ HGSJNOGe GdcJGHI hGdJhbjY Ydi GdeMQQGJ GdEdcJQhfjI aj GdELQGAGJ GdbVGFjI, dPdc QcRJ gPg GdOQGSI Ydi JMdjd hGbY GSJNOGe JcfhdhLjG GdMGShH Ydi GdEfJQfJ aj SjGb GdELQGAGJ GdbVGFjI GdeNJdaI dGSJNdGU eaghe eMOO ddJbGVj GdEdcJQhfj hJMOjO NUGFUg hYQV GdbhGYO GdbGfhfjI GdJj JVef eeGQSI Jdc GdELQGAGJ ef NdGd GdCfXeI GdEdcJQhfjI aj GdJTQjYGJ GdebGQfI heYGdLI GdeQGMd GdeNJdaI ddNUheI GdbVGFjI YHQ GdEfJQfJ GHJOGA ef JMQjQ YQjVI GdOYhi hGfJgGA HUOhQ GdMce GdbVGFj hGdWYf ajg jYHQ GdEfJQfJ, Ydjg JfGhdJ gPg GdOQGSI GdJYQja HGdJbGVj GdeOfj YHQ GdEfJQfJ hHjGf ELQGAGJg hGdCMcGe GdbVGFjI hGdWYf YHQ GdEfJQfJ(B.s
(3GdCUd CWQhMI (B((3OcJhQGg(B)(3, ETQGa GdOcJhQ bUj SdeGf gdGd, LGeYI UdGM GdOjf(B-(3CQHjd(B.s
(3HHdjhLQGajI (B: (3UaMI (B319-344.s
Keywords: (3GdJOGYj CeGe GdeMGces -- (3eYGdLI HjGfGJs; (3GdOYhi GdeOfjIs -- (3eYGdLI HjGfGJs